Matos Moctezuma Eduardo, Messico. La scoperta del passato (Altre Modernità, 2011)
Matos Moctezuma Eduardo, Messico. La scoperta del passato, (Corpus Precolombiano, Jaca Book, Milano, 2010, 386 pp. ISBN 9788816604360)di Davide Domenici